Analysis of crosstalk in the mechanomyographic signals generated by forearm muscles during different wrist postures. Issue 6 (28th April 2015) - Islam, Anamul; Sundaraj, Kenneth; Ahmad, R. Badlishah; Sundaraj, Sebastian; Ahamed, Nizam Uddin; Ali, Md. Asraf
ABSTRACT Introduction In this study, we analyzed the crosstalk in mechanomyographic (MMG) signals generated by the extensor digitorum (ED), extensor carpi ulnaris (ECU), and flexor carpi ulnaris (FCU) muscles of the forearm during wrist flexion (WF) and extension (WE) and radial (RD) and ulnar (UD) deviations. Methods Twenty right‐handed men (mean ± SD age = 26.7 ± 3.83 years) performed the wrist postures. During each wrist posture, MMG signals were detected using 3 accelerometers. Peak cross‐correlations were used to quantify crosstalk. Results The level of crosstalk ranged from 1.69 to 64.05%. The wrist postures except the RD did not influence the crosstalk significantly between muscle pairs. However, muscles of the forearm compartments influenced the level of crosstalk for each wrist posture significantly. Conclusions The results may be used to improve our understanding of the mechanics of the forearm muscles during wrist postures. Muscle Nerve51: 899–906, 2015